Knowledge translation of climate change research into public health action: a scoping review - Mulopo, Chanelle; Onkoba, Nyamongo; Abimbola, Samuel; Baltaci, Ezgi; Wright, Caradee Y.; Schmidt, Bey-Marrie (Frontiers in Public Health, 2025)
BackgroundThere are gaps in translating climate change research into public health action at the global level. Knowledge translation refers to the methods used to bridge the gap between knowledge and action. Given the significant impacts of climate change on health, it is essential to integrate climate research into health decision-making processes. This integration ensures that evidence effectively informs policies and practices at all levels, leading to more timely, equitable, and impactful public health responses.ObjectiveThis scoping review examines key approaches and identifies gaps in knowledge translation methods for integrating climate change research into public health decision-making.MethodsA systematic search of the literature was conducted in PubMed, CINAHL, and Scopus using a predefined search string to identify studies on climate change and health published between January 1, 2003, and March 1, 2024, with no geographic restrictions. Retrieved articles were screened and data extracted using Covidence software. Thematic analysis was performed in ATLAS.TI employing Braun and Clark’s six-step method. The identified knowledge translation approaches were categorized according to the Cochrane Knowledge Translation Framework.FindingsOur findings highlight five primary knowledge translation approaches: (1) monitoring the coverage of climate change and health across media, scientific literature, and government responses; (2) engaging citizens of all ages in participatory activities to address local climate challenges and co-develop policy solutions; (3) integrating knowledge generation, synthesis, and dissemination for effective communication; (4) emphasizing advocacy and education to foster collaborations and gain support from decision-makers; and (5) leveraging health impact assessment tools to guide decision-making related to climate change and health. Nonetheless, we did not find any primary studies on climate change research and knowledge translation in Low- and Middle-Income Countries (LMICs).ConclusionThere is a need for primary studies on the knowledge translation of climate change research, especially in relation to adaptation, into meaningful public health actions that can inform decision-making and contribute to building climate-resilient health systems in LMICs.